2007
DOI: 10.1096/fj.07-9566com
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and structural studies of novel coenzyme‐substrate analogs of human histidine decarboxylase

Abstract: Histamine, a biogenic amine with important biological functions, is produced from histidine by histidine decarboxylase (HDC), a pyridoxal 5'-phosphate-dependent enzyme. HDC is thus a potential target to attenuate histamine production in certain pathological states. Targeting mammalian HDC with novel inhibitors and elucidating the structural basis of their specificity for HDC are challenging tasks, because the three-dimensional structure of mammalian HDC is still unknown. In the present study, we designed, synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
1
21
0
3
Order By: Relevance
“…The pyruvamide-dependent AADCs include S-adenosylmethionine (SAM) DC 74 from all three kingdoms of life (also central to the polyamine biosynthetic pathway), aspartate α-DC 75 (key step in coenzyme A biosynthesis, potential antibiotic target), phosphatidyl serine DC 76 (phospholipid biosynthesis) as well as other variants of both histidine DC 77 and arginine DC. 78 In this context, the methodology/protection strategy reported here shows real promise for building potential new inhibitors for ODC (lysine chemistry here) and for aromatic AADC (tyrosine and tryptophan side chains established here vs. the DOPA and 5-hydroxytryptophan side chains that presumably would target this active site).…”
Section: Discussionmentioning
confidence: 99%
“…The pyruvamide-dependent AADCs include S-adenosylmethionine (SAM) DC 74 from all three kingdoms of life (also central to the polyamine biosynthetic pathway), aspartate α-DC 75 (key step in coenzyme A biosynthesis, potential antibiotic target), phosphatidyl serine DC 76 (phospholipid biosynthesis) as well as other variants of both histidine DC 77 and arginine DC. 78 In this context, the methodology/protection strategy reported here shows real promise for building potential new inhibitors for ODC (lysine chemistry here) and for aromatic AADC (tyrosine and tryptophan side chains established here vs. the DOPA and 5-hydroxytryptophan side chains that presumably would target this active site).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [14] showed that the pyridoxyl-histidine methyl ester (PHME) acts as a potent transition-state inhibitor of histidine decarboxylase (hHDC) in human cells. When PHME was applied to cultured P. falciparum no significant growth inhibition was observed; similar to the result obtained with the pyridoxine analog deoxypyridoxine, although the latter was previously reported to be an effective inhibitor in a different system [21].…”
Section: Discussionmentioning
confidence: 99%
“…The active site model of Pf ODC with PPT3 and PPT5 was generated on the basis of the known 3D coordinates of the complex of Pf ODC with PLP-DFMO followed by energy minimization with the InsightII/Built module (steepest descents, up to a maximum derivative of 20 kcal/mol, consistent valence force field, CVFF). The structures were further optimized by energy minimization using the InsightII/Discover module (conjugation gradient, until a maximum derivative of 0.01 kcal/mol was reached, CVFF) according to Wu et al [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither agent has been clinically used. Epigallocatechin gallate from green tea (20) and pyridoxyl histidine methyl ester (21) were recently found to act as potent HDC inhibitors; however, the possibility of side effects, in vivo efficiency, and specificity for HDC of these inhibitors have not been assessed, making them unavailable for clinical use. Detailed information on the structure of HDC would facilitate the development of HDC inhibitors with high affinity and specificity.…”
mentioning
confidence: 99%